Policy implications for the improvement of technology transfer and commercialization process in the Indian context. Issue 1 (4th March 2019) - Sheth, Bhavisha P.; Acharya, Satya Ranjan; Sareen, S.B.
Abstract : Purpose: Scientific innovation has resulted in the development of newer technologies for the betterment of humankind. Academic and research organizations are the places where these technologies are actually ideated and/or invented. However, the process of technology transfer and its eventual successful commercialization covers many other facets, in addition to the scientific research alone. This study aims to draw attention towards certain policy gaps and thereby suggest plausible solutions for the improvement of technology transfer process in the Indian context. Design/methodology/approach: Here, the authors present an extensive Web survey of technologies available for transfer/commercialization in 12 major Indian research organizations, namely, Indian Council of Agricultural Research (ICAR), Indian Council of Medical Research, Council of Scientific and Industrial Research, Defence Research and Development Organisation, Department of Atomic Energy, Department of Biotechnology, Indian Space Research Organisation, Indian Institute of Technology (IIT) Bombay, Indian Institute of Science Bangalore, IIT Delhi, IIT Kharagpur and IIT Kanpur. Findings: A total of 2, 921 technologies were found to be available with respect to the above-mentioned organizations, with the highest of these in agricultural sciences and the maximum reported by ICAR. Research limitations/implications: Certain significant policy interventions of this study include the need of a central framework for deposition, management and dissemination of institutionally developed technologies. More attention and support is required for the technologically less developed research areas, and there is a need for the promotion of funding mechanisms for the prototype development, in addition to the already available funding schemes for other stages of technology commercialization. Practical implications: Hence, the successful commercialization of the innovation from the Indian research labs requires the restructuring of the existing policies to eventually facilitate the economic growth of the nation. Originality/value: This study discusses the major policy gaps of the Indian technology transfer process. For this, an extensive Web survey was carried out to enlist the various technologies available for transfer and commercialization in India from 12 major research organizations. The study presents the results and some major policy implications of the technology transfer and commercialization process in the Indian context.